PENGARUH LAMA PEREBUSAN PADA PEMBUATAN MINUMAN HERBAL DAUN SAWO (Manilkara zapota) TERHADAP KARAKTERISTIK DAN DAYA HAMBAT PERTUMBUHAN Escherichia coli - Dewi Anggraini, Ida Ayu Ketut; Trisna Darmayanti, Luh Putu; Sugitha, I Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 3 (2020): Jurnal ITEPA, 2020)
This research was conducted with the aim to determine the effect of boiling time on making sapodilla herbal drinks on the characteristics and growth of E. coli bacteria and boiling time which can produce the best characteristics and inhibition. This study used a Completely Randomized Design (CRD) with treatment, which was heated at 60 ° C with a boiling time consisting of 5 levels of 10, 20, 30, 40, and 50 minutes. The treatment was repeated 3 times to produce 15 experimental units. The data is then analyzed with variance and if there is an influence between treatment levels then it is continued with the Duncan test. The inhibition test was carried out using the paper disc method. The results showed that the boiling time had a significant effect (P <0.05) on total phenols, tannins, flavonoids, E. coli inhibition, the color and taste of brown herbal drinks. The best boiling time is 30 minutes, with inhibition of 13.3 mm with phenol, tannin and flavonoid content respectively 3.687 mg / 100 g, 2.036 mg / 100 g, and 4.233 mg / 100 g with a bright orange color and is rather preferred, ordinary aroma, rather bitter and ordinary taste, and overall acceptance are rather frowned upon.